2013
DOI: 10.1179/2045772312y.0000000080
|View full text |Cite
|
Sign up to set email alerts
|

A peculiar complication of suprapubic catheterization: Recurrent ureteral obstruction and hydronephrosis

Abstract: Context: Suprapubic cystostomy (SPC) catheterization is a common and important technique for the management of vesicular drainage, especially in patients with neurogenic bladder. Some serious complications include bowel perforation and obstruction. Findings: A 55-year-old man with C6 American Spinal Injury Association B tetraplegia and a urethral stricture requiring a chronic SPC was admitted for recurrent urosepsis. Computed tomography (CT) of the abdomen revealed severe right hydronephrosis and hydroureter d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
16
0
4
Order By: Relevance
“…Although suprapubic catheters have many advantages, there are also several important risks and limitations to note. The most common are risk of visceral injury (bowel perforation),6,15 bleeding, hematuria, and UTI 12,16. Sheriff et al reviewed 185 cases and identified 2.7% incidence of bowel perforation, with one fatal outcome,17 but the National Patient Safety Agency placed the figure at 0.15% 18.…”
Section: Discussionmentioning
confidence: 99%
“…Although suprapubic catheters have many advantages, there are also several important risks and limitations to note. The most common are risk of visceral injury (bowel perforation),6,15 bleeding, hematuria, and UTI 12,16. Sheriff et al reviewed 185 cases and identified 2.7% incidence of bowel perforation, with one fatal outcome,17 but the National Patient Safety Agency placed the figure at 0.15% 18.…”
Section: Discussionmentioning
confidence: 99%
“…L'obstruction était secondaire à l'inflammation méatale induite par l'extrémité du cystocathéter. Cette dernière a disparu après remplacement de celui-ci par une sonde vésicale [5].…”
Section: Discussionunclassified
“…Bij de meerderheid van deze gevallen betreft het ook een transurethrale, en geen suprapubische katheter [3][4][5][6]. Daarnaast is het belangrijk om een onderscheid te maken tussen obstructie door plaatsing van een behoorlijke lengte van de katheter in de ureter enerzijds, en obstructie ontstaan door (herhaaldelijke) migratie van de tip van de katheter in een van de ostia anderzijds, een complicatie die wel vaker wordt genoemd [7][8][9][10][11][12].…”
Section: Discussieunclassified
“…Deze principes omvatten het bevestigen van urinedrainage uit de katheter alvorens de ballon op te blazen, controleren of de lengte van de katheter buiten het lichaam correct is, en het ledigen van de ballon en herpositioneren van de katheter bij plotse pijn. Een ander advies voor artsen en verpleegkundigen is het markeren van de lengte van de katheter die in situ is, en de corresponderende lengte aangeven op de nieuwe katheter, zodat de zorgverlener weet tot welke diepte de katheter opgevoerd kan en mag worden [3][4][5][11][12][13]. Als preventieve maatregel wordt in de literatuur meermaals het wisselen over een voerdraad vermeld en dit is inderdaad een manier om een katheterwissel vlotter te laten verlopen, maar ook deze benadering zal plaatsing van een katheter in een ureter niet altijd kunnen vermijden [3,5,11,12].…”
Section: Discussieunclassified